Epidemiology and demographic risk factors for myopia in Ghana: a 5-year retrospective study - Samuel Kyei; Rexford Kwasi Gyaami; John Baptist Abowine; Ebenezer Zaabaar; Augustine Nti; Kofi Asiedu; Samuel Bert Boadi-Kusi; Bismark Owusu-Afriyie; Frank Assiamah; Anthony Armah (Springer, 2024)
Abstract Purpose To explore the epidemiology and demographic risk factors for myopia among a clinical sample. Methods In a hospital-based retrospective study, eligible subjects were grouped into either myopia or non-myopia. Demographic data, including age, sex, occupation, area of residence, region of residence, and ethnicity, were analysed. Other clinical information analysed included the degree of myopia and intervention provided for the myopia. Results Overall, the medical records of 15807 patients were retrieved between January 2015 and December 2019, with 50.9% being males. The mean ± SD age of the patients was 42.81 ± 18.99 years. A total of 44.4% of the patients were myopic. Age, type of ethnic group, occupation, and area of residence were associated with myopia. Demographic risk factors for myopia included occupations such as professionals (OR: 2.93; 95% CI 2.44-3.52), technicians and associated workers (OR: 6.71; 95% CI 5.15-8.74), service workers (OR: 11.74; 95% CI 9.62-14.33), skilled agriculture and fishery (OR: 1.88; 95% CI 1.41-2.50), craft workers (OR: 3.41; 95% CI 2.75-4.25), armed forces (OR: 10.26; 95% CI 7.54-13.97), students (OR: 3.49; 95% CI 2.76-4.42), the unemployed (OR: 6.64; 95% CI 5.44-8.11), as well as Ewe (OR: 1.46; 95% CI 1.17-1.82) and Ga-Adangbe (OR: 1.28; 95% CI 1.05-1.54) ethnicities. Conclusion Ewe and Ga-Adangbe ethnicities, and specific occupations are risk factors for myopia.